The Implementasi Program Religius dalam Pembentukan Karakter Siswa di Sekolah Dasar : Analisi Peran Guru, Kepala Sekolah dan Dukungan Orangtua: Jurnal Kependidikan - Qothrunada Mazaya Mukhtar; Rita Efendi Septiana; Wahyu Agil Munawar; Yarti (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study examines the implementation of religious programs in shaping students’ character in elementary schools by analyzing the roles of teachers, principals, and parental support. A qualitative approach was employed to explore the dynamics of program implementation through observations, interviews, and documentation. The findings reveal that teachers play a central role as role models by consistently integrating religious values into daily routines, instructional activities, and personal guidance. Principals provide structural support through policy formulation, facility provision, and the reinforcement of a school culture grounded in religious values. Parents strengthen the internalization of these values through home-based practices and active collaboration in school activities. The religious programs contribute positively to the development of students’ discipline, responsibility, empathy, and spiritual awareness. These results highlight the importance of continuous synergy between school and family in fostering a holistic and religiously oriented educational environment.